Board Characteristics and Disclosure of Environmental Sustainability Reports in Indonesia: Moderation Effects of Political Connection - Claudya, Ursula; Raharja, Surya (KINERJA, 2023)
The purpose of this study is to examine whether the characteristics of the board of commissioners in Indonesia affect the level of corporate environmental sustainability reporting, as well as to examine the moderating effect of political connections on the disclosure of environmental sustainability reports. The sample used was 80 companies listed on the Indonesia Stock Exchange in 2019-2021. The analysis technique used is Moderated Regression Analysis to examine the moderating effect of political connections and the effect of board characteristics on the disclosure of environmental sustainability reports. The results show that the board size variable has a significant positive effect on the disclosure level of environmental sustainability reports. Additionally, this study found that political connections weaken the influence of gender diversity on the disclosure of environmental sustainability reports. These findings provide valuable insights and evaluation for stakeholders aiming to implement good corporate governance practices to enhance environmental sustainability reporting performance. They can also serve as input for the government in developing guidelines for corporate sustainability reporting.